2022
DOI: 10.1039/d2ta07229g
|View full text |Cite
|
Sign up to set email alerts
|

A highly-active Zn0.58Co2.42O4 spinel oxide as a promising cathode for proton-conducting solid oxide fuel cells

Abstract: The highly-active and chemically stable Zn0.58Co2.42O4 cathode allows a record-high fuel cell performance for proton-conducting solid oxide fuel cells using spinel oxide cathodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The peak power densities of PBCsC single cells have surpassed those of most of the cells recently reported (Figure d). The current densities of PBCsC cells at 1.3 V are outperforming among them under the similar measured conditions (Figure e). ,,,, ,, Meanwhile, the electrochemical performance of the single cells with the PBCsC air electrode is higher than most of the recently reported air electrodes in the FC mode and EC mode. The details for the comparisons of the cells are displayed in Table S4 and Table S5.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The peak power densities of PBCsC single cells have surpassed those of most of the cells recently reported (Figure d). The current densities of PBCsC cells at 1.3 V are outperforming among them under the similar measured conditions (Figure e). ,,,, ,, Meanwhile, the electrochemical performance of the single cells with the PBCsC air electrode is higher than most of the recently reported air electrodes in the FC mode and EC mode. The details for the comparisons of the cells are displayed in Table S4 and Table S5.…”
mentioning
confidence: 58%
“…The D * chem values of PBC and PBCsC are 2.64 × 10 –5 and 9.01 × 10 –5 cm 2 s –1 at 650 °C. The larger D * chem value of PBCsC illustrates that it may have a better oxygen diffusion kinetics than PBC . According to the above analyses, it is suggested that the enhanced electrocatalytic activity of the PBCsC electrode is likely attributed to the A-site dopant (Cs), thus generating more oxygen vacancies and improving the surface exchange kinetics.…”
mentioning
confidence: 95%
“…A conventional combustion process was conducted to prepare La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−d (LSCF) powders using citric acid (CA, 99.5%) as the combustion aid and ethylene diamine-acetic acid (EDTA, 99.5%) as the complexing agents. 42,43 The starting chemicals were La 2 O 3 (99.99%), Sr(NO 3 ) 2 (99.5%), Co(NO 3 ) 2 -$6H 2 O (98.5%), and Fe(NO 3 ) 3 $9H 2 O (98.5%). These chemicals were dissolved to form an aqueous solution, in which the combustion agents were subsequently added according to the molar ratio of 2 : 1 : 1 for CA, EDTA, and the total metal ions.…”
Section: Powder Synthesis and Composite Formationmentioning
confidence: 99%
“…In recent years, one primary focus of SOFCs research has been on proton-conducting SOFCs (H-SOFCs) [6,7] because H-SOFCs with proton-conducting electrolytes can reduce the operating temperature of SOFCs and hence increase their lifetime [8][9][10]. Additionally, H-SOFCs minimize fuel dilutions because water is produced at the cathode [11,12]. In contrast, water is produced at the anode side for traditional SOFCs using oxygen-ion conducting electrolytes, which can combine with the fuels and reduce efficiency.…”
Section: Introductionmentioning
confidence: 99%